SAT0491 PSORIASIS ASSOCIATED WITH MONOCLONAL-ANTIBODY-TNF-Α INHIBITORS VS. FUSION PROTEIN ETANERCEPT IN JUVENILE IDIOPATHIC ARTHRITIS PATIENTS - ANALYSIS OF THE BIKER REGISTRY. (2nd June 2020) - Zimmer, A.; Klein, A.; Horneff, G.
Abstract : Background: Although efficacy of Tumor necrosis factor inhibitors (TNFi) for treatment of psoriasis is well established, patients may develop psoriasis for the first time while on TNFi as a paradoxical effect. Few data are available in patients with juvenile idiopathic arthritis (JIA). Objectives: To analyze the incidence of psoriasis in TNFi – treated JIA patients and to identify associated factors. Methods: Safety data from patients registered in the German Biologics registry (BIKeR) were analyzed. Cohorts of patients were grouped by treatment: any or multiple TNFi, single TNFi, biologics other than TNFi and no biologics (control group on methotrexate (MTX) only). TNFi-associated psoriasis was defined as incident diagnosis of psoriasis after starting a TNFi. Patients with personal history of psoriasis prior to TNFi therapy were excluded. Rates and events per 100 patient-years (PY) of exposure were calculated using AEs reported after first dose under therapy and under the age of 18 years. Rates were compared by X2-test, event rates by Wald test. Results: A total of 4149 treatment episodes with TNFi (Etanercept, Adalimumab, Golimumab, Infliximab), with a total exposure time of 8437 PY, were identified. There were 676 treatments with a non-TNFi- biologic (Tocilizumab, Abatacept, Anakinra, Canakinumab) with a total exposure time of 1112 PY. MTX monotherapy was conducted in 1692 patients with a total exposure time of 3971 PY. In total, 31 patients were diagnosed with incident psoriasis on JIA-treatment (Table 1 ). The mean duration of therapy until incident psoriasis was 2.2 (± 1.8) years. Multiple psoriatic skin manifestations were observed. Psoriasis events were significantly more frequent in any or multiple TNFi compared to MTX-monotherapy, and specifically in the subgroup of TNF-antibody treatment (all) or Adalimumab compared to MTX or Etanercept (Table 2 ). Interestingly, psoriasis events were also observed with non-TNFi at high frequency. At occurrence of the event, patients exposed to biologics received MTX or steroids less frequently compared to the total patient cohort and had a higher JADAS10. Conclusion: Our findings demonstrate a higher incidence of psoriasis in monoclonal-antibody-TNFi-treated JIA-patients, whereas in Etanercept-treated JIA patients no significant increase was detected. On average, psoriasis-manifestation occurred more than two years after treatment-initiation. Teenage females with ANA-positivity were most often affected. Disclosure of Interests: Angela Zimmer: None declared, Ariane Klein Consultant of: Celgene, Gerd Horneff Grant/research support from: AbbVie, Chugai, Merck Sharp & Dohme, Novartis, Pfizer, Roche, Speakers bureau: AbbVie, Bayer, Chugai, Merck Sharp & Dohme, Novartis, Pfizer, Roche